Bovine colostrum enriched with lyophilized bovine colostrum stimulates intestinal epithelium renewal of Holstein calves in the first days of life. Issue 2 (10th July 2017) - Kindlein, L.; Moretti, D. B.; Pauletti, P.; Bagaldo, A. R.; Rodrigues, A. P. O.; Machado‐Neto, R.
Summary: Consumption of a second meal of colostrum with high quality could contribute to the intestinal epithelium development, especially if there is poor supply of colostrum just after birth. The effect of a second colostrum meal was evaluated on histomorphometry of the intestinal mucosa of newborn Holstein calves fed with high‐ and low‐quality first colostrum. Seventy‐two calves were fed with a first colostrum meal with high (HFM, close to 100 mg/ml) or low (LFM, close to 30 mg/ml) IgG concentration. At 12 hr of life, three treatments of second colostrum feeding were applied to the calves either fed high or low first colostrum: calves fed with low (LOW—close to 30 mg/ml) or high (HIGH—close to 100 mg/ml) IgG concentration; and colostrum enriched with lyophilized bovine colostrum with high IgG concentration (ENRICHED—higher than 120 mg/ml), resulting in six groups. Intestinal samples were collected after 24 and 72 hr of life. In the distal jejunum and ileum, LOW showed higher villus height than ENRICHED ( p < .05). In the distal jejunum, greater villus perimeter was observed in the LOW compared to ENRICHED at 24 hr ( p < .05). In ileum, LFM showed higher villus perimeter compared to HFM ( p < .05). LOW showed the highest villus height‐to‐crypt depth ratio in the medium and distal jejunum and ileum, p < .05. ENRICHED and HFM showed decreased muscle layer thickness in the proximal and distal jejunum respectively ( p < .05). The results reveal that the high concentration of total solids, crude protein, IgG and IGF‐I of colostrum with high quality worsened the absorptive area, but may have stimulated the activity of cell division in intestinal crypts. Considering the present results, bovine colostrum enriched with lyophilized bovine colostrum stimulates intestinal epithelium renewal of Holstein calves in the first days of life.